FRAMEWORK TO ENHANCE THE IMPLEMENTATION OF QUALITY MANAGEMENT SYSTEM IN CONSTRUCTION - Othman, Idris; Mohamad, Hisham; Napiah, Madzlan; Mohd Ghani, Siti Norfarahhanim; Zoorob, Salah (International Journal of Engineering Technologies and Management Research, 2018)
In Malaysia, construction industry plays an important role in benefitting towards the development of country’s economy as well as providing the necessary infrastructure and enhanced facilities for social comfort. Despite these contributions, this thriving industry is responsible for generating an excessive amount of construction waste and numerous cases on delaying which then tarnish the reputation of the company. Therefore, this study evaluates the factors affecting the implementation of quality management system practices in construction project through the application of structured questionnaire and case study of high rise construction project to come out with a structured framework that can enhance the quality management system in construction project. The statistical techniques used to evaluate the data obtained are relative importance index (RII) and Average Index (AVI), while cronbach’s alpha is used to measure the significant between three different groups of respondents, the reliability and validity of the study.